Exploring the Perception of Library and Information Science Programme among Undergraduates Students of Umaru Musa Yar’adua University, Katsina - Badiya , Hassan Sada; Lawal, Umar (MiddleBelt Journal of Library and Information Science, 2016)
This paper explored the perception of library and information science programme among undergraduate students of Umaru Musa Yar’adua University, Katsina. It aimed to determine how other undergraduate students of other departments perceive LIS programme and the factors that influenced their perceptions. Qualitative research method was adopted and a case study research design was used for the study. Undergraduate students from other departments formed the population of the study where- 20 students were drawn purposively from all the 4 faculties as sample size. Interview was used as instrument for data collection. The study found that most respondents perceive LIS programme as a less activity course; not a recognised programme; an excellent course for women while others see it as an interesting course to pursue in the university. It concluded that students from other programmes viewed LIS programme with mixed feelings. The need for University management to set up career guidance and counselling units with desk officers in all faculties to guide, educate and enlighten students about the prospects and career opportunities of library and information science in Umaru Musa Yar’adua University, Katsina was recommended. This will broaden students understanding and horizon in such a way that LIS programme is not misinterpreted; thus leading to misconceptions and inferiority complex among students.